A Class of Fractional Evolutionary Equations. Issue 1 (December 2013) - Picard, Rainer
Abstract A well‐posedness result for a time‐shift invariant class of evolutionary operator equations involving material laws with fractional time‐derivatives is considered and exemplified by an application to a fractional Kelvin‐Voigt type model. (© 2013 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)